Children"s Modes of Listening to Music at Home and at School - Boal-Palheiros, G. (2004)
This study investigated how children listen to music, by examining relationships different modes of listening and different contexts, home and school. It also looked tal and cultural perspectives, by comparing children from different age levels and The 120 participants were British and Portuguese children aged 9-10 years, attending schools, and 13-14 years, attending secondary schools. Children responded interview with open-ended questions, concerning their modes of listening to music at school. Findings showed that children's modes of listening imply various levels emotional involvement with music, and depend on the context, which may be related junctions of music. At home, few children listened to music as a main activity. listening and performing (singing, dancing), or accompanying a variety of non-(studying, playing games). At school, children listened to music often while doing ties (analysis, performing), moderately as a main activity, but rarely while doing activities. There were no relevant national differences, and age differences resulted specific teaching strategies at each school level.